The symbols of the National-Catholicism. A look at school photography during Francoism (1950-1959) - Sanz Simón, Carlos (Historia y Memoria de la Educación, 2019)
The dictatorship of Francisco Franco brought with it an aggressive process of nationalization that was especially evident in education. Having liquidated the republican project, the regime established an education based on the exaltation of ethnicity, the homeland and the Catholic religion. These would be the pillars of the self-styled New State, which would be made explicitly visible in schools, both inside and outside. This article presents an analysis of the symbology of National-Catholicism, and attempts to delve into its presence or absence in terms of three categories: the ownership of the centers —classified in this study as religious or non-religious—, their geographical location and the link between these symbols a nd the students according to their sex. In order to do so, we have used the photographs contained in the collection of the teacher-training memoirs "Romero Marín", located in the Museum/Laboratory of History of education «Manuel Bartolomé Cossío» of the Complutense University of Madrid. They have allowed us to observe certain tendencies that relate to the proposed categories, in particular the use of the religious centers’ own symbology to the detriment of strictly political representations, the appearance of some centers’ own symbols in some regions and an explicit differentiation in the relationship between symbols and the boys and girls educated during the fifties.